2008
DOI: 10.1021/ja803665q
|View full text |Cite
|
Sign up to set email alerts
|

Hydrated Alkali-Metal Cations: Infrared Spectroscopy and ab Initio Calculations of M+(H2O)x=2−5Ar cluster ions for M = Li, Na, K, and Cs

Abstract: A delicate balance between competing and cooperating noncovalent interactions determines the three-dimensional structure of hydrated alkali-metal ion clusters. With a single water molecule hydrating an ion, the electrostatic ion...water interaction dominates. With more than one water molecule, however, water...water hydrogen-bonding interactions compete with the ion...water interactions to influence the three-dimensional structure. Infrared photodissociation spectra of M(+)(H2O)(x=2-5)Ar (with effective temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
286
4
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(321 citation statements)
references
References 53 publications
26
286
4
5
Order By: Relevance
“…Under these circumstances, alkali ons attract and localize the lone pairs of oxygen and strengthen the OÀH···X À Hb, constituting the cooperative effect of cations and anions M + ···OÀH···X À (in which M = Li, Na, K, Cs and X = F, Cl, Br, I), which was already demonstrated by high-level ab initio [19] and density functional theory [20] simulation studies, and is herein shown experimentally for the first time ( Figure 2 lower than expected blueshift within the alkali series. Only a few studies showed that Cs + can deviate from monotonic spectral trends in alkali solutions [8,21] and our data do not provide enough details to clarify specificities of CsCl hydration. Therefore, blueshifts correlate primarily with trends in halide charge density but for the same halide ion (Cl À ) they are strongly influenced by the cooperative effect of alkali ions.…”
Section: Raw Spectracontrasting
confidence: 76%
“…Under these circumstances, alkali ons attract and localize the lone pairs of oxygen and strengthen the OÀH···X À Hb, constituting the cooperative effect of cations and anions M + ···OÀH···X À (in which M = Li, Na, K, Cs and X = F, Cl, Br, I), which was already demonstrated by high-level ab initio [19] and density functional theory [20] simulation studies, and is herein shown experimentally for the first time ( Figure 2 lower than expected blueshift within the alkali series. Only a few studies showed that Cs + can deviate from monotonic spectral trends in alkali solutions [8,21] and our data do not provide enough details to clarify specificities of CsCl hydration. Therefore, blueshifts correlate primarily with trends in halide charge density but for the same halide ion (Cl À ) they are strongly influenced by the cooperative effect of alkali ions.…”
Section: Raw Spectracontrasting
confidence: 76%
“…There is a small decrease in SFG intensity with increasing concentration of MgCl 2 for concentrations up to 2.1 M. However, the number of free OH as seen in the MD simulations increases with concentration. This discrepancy has been previously attributed to red-shifting of free OH in the first solvation shell of Mg 2þ out of the peak attributed to other free OH contributions, as well as to perturbations of the intensity of free OH stretches by ions (23,24). For 3.1 M and 4.7 M MgCl 2 , a larger decrease in SFG intensity of the free OH peak is observed relative to the lower concentrations.…”
Section: Discussionmentioning
confidence: 79%
“…However with each stepwise addition of Ar, the changes are significant; the B conformer becomes the dominant conformer sampled in our experiment. Previous studies in our group on hydrated alkali metal ion systems [18] have shown that the argon evaporation method allows low energy configurations of the neutral clusters to interact with the approaching ion. Rapid argon evaporation effectively dissipates the kinetic energy, leaving the resulting complexes with very low internal energies and, in some cases, in non-global minimum energy conformations.…”
Section: Resultsmentioning
confidence: 99%